2020
DOI: 10.1080/26395940.2020.1713895
|View full text |Cite
|
Sign up to set email alerts
|

Load characteristics and inhalation risk assessment of benzene series (BTEX) pollutant in indoor air of Ghalyan and/ or cigarette cafes compared to smoking-free cafes

Abstract: Arfaeinia (2020) Load characteristics and inhalation risk assessment of benzene series (BTEX) pollutant in indoor air of Ghalyan and/ or cigarette cafes compared to smoking-free cafes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Moreover, the mean benzene concentration was higher in the upper residential units in which the residents were smokers, as compared to other units. Similar results have been reported by previous studies in the production of benzene with smoking [ 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the mean benzene concentration was higher in the upper residential units in which the residents were smokers, as compared to other units. Similar results have been reported by previous studies in the production of benzene with smoking [ 20 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…They found that the cafes located in the basement, due to poor ventilation or the complete lack of it, accumulate large amounts of these pollutants and further endanger the health of customers. In addition, the risk assessment showed that the carcinogenic and non-carcinogenic risk levels of the air inside the tobacco cafes exceeded the safe limits recommended by the EPA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that toluene is a toxic compound that can cause adverse human health endpoints such as headaches, central nervous system damage, loss of control and consciousness, and even death from short-term exposure [ 39 ]. Therefore, the discharge of tobacco waste containing large amounts of toluene and/or other BTEX compounds into the environment may have negative impacts on human health as well as aquatic organisms [ 7 ]. Unfortunately, no similar reports were found that examined the BTEX concentrations in the waste products of flavored and local tobacco samples to compare the findings of the current study with.…”
Section: Resultsmentioning
confidence: 99%
“…Waterpipe smoking involves passing air heated with charcoal over tobacco (either local or flavored) to create smoke [ 6 ]. This smoke is passed through water to cool and moisten the smoke to make it more facile for the consumer to inhale [ 7 ]. Waterpipe (their equivalent names include narghile, waterpipe, hubble-bubble, arghile, arguile, and shisha) are now commonly used to smoke tobacco across the Eastern Mediterranean, Africa, Asia, the United States, and other Western countries, especially among youth and young adults [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the risk assessment of exposure to BTEX compounds in the indoor air of cafes has shown that the carcinogenic and non-carcinogenic risks of these compounds exceed the safe limits recommended by the EPA. Therefore, more studies and monitoring should be done on these environments and appropriate control policies should be set for this public health threat (14,16).…”
Section: Discussionmentioning
confidence: 99%